2021
DOI: 10.1029/2020jb019560
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Strain Patterns Associated With Normal, Drought, and Heavy Precipitation Years in California

Abstract: We invert continuously operating Global Positioning System (cGPS) data obtained between 2007 and 2019 to quantify non steady‐state horizontal strain anomalies in California. Our long‐wavelength transient strain model shows seasonal and multiannual variations in horizontal strain anomalies within the plate boundary zone. During the summer, in general, a zone of extensional dilatation develops along the San Andreas Fault zone and Sierra Nevada, whereas contractional dilatation develops along the Eastern Californ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…The no-length-change directions (strikes of vertical strike-slip faults), upon which we calculate stress changes (King et al, 1994), are in accord with the orientations of strike-slip focal mechanism solutions (Hauksson et al, 2012;Yang et al, 2012) and the surface trace of strike-slip Quaternary faults (Jennings, 1994;Nicholson et al, 2017;Shaw et al, 2015) within the ECSZ-WL transition zone (see Figure S17 from Kim et al [2021]). A more complex geometry of the faults, however, will have an influence on the accuracy of our results.…”
Section: The Accuracy Of Our Assumptions In the Modelmentioning
confidence: 61%
See 3 more Smart Citations
“…The no-length-change directions (strikes of vertical strike-slip faults), upon which we calculate stress changes (King et al, 1994), are in accord with the orientations of strike-slip focal mechanism solutions (Hauksson et al, 2012;Yang et al, 2012) and the surface trace of strike-slip Quaternary faults (Jennings, 1994;Nicholson et al, 2017;Shaw et al, 2015) within the ECSZ-WL transition zone (see Figure S17 from Kim et al [2021]). A more complex geometry of the faults, however, will have an influence on the accuracy of our results.…”
Section: The Accuracy Of Our Assumptions In the Modelmentioning
confidence: 61%
“…Kim et al (2021) showed that it is possible using cGPS data to extract short-wavelength (tens of km), high-amplitude horizontal strain anomaly patterns that are superimposed on long-wavelength (hundreds of km) strain anomaly patterns in California and western Nevada. The long-wavelength horizontal nontectonic strain solution can be explained as the Earth's elastic response to the large-scale hydrologic loading in the plate boundary zone (Kim et al, 2021). We also find that the short-wavelength horizontal strain patterns (Figures S6a and S6b) across the ECSZ-WL transition zone are superimposed on the long-wavelength patterns (Figures S6c and S6d).…”
Section: Possible Dynamic Sources Responsible For the Seasonal Strain...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several major earthquakes occurred during the time period considered in the study area (notably the 1994 Northridge, 1999 Hector Mine, 2004 Parkfield, 2010 El Mayor‐Cucapah, and 2019 Ridgecrest earthquakes). There is also evidence that multi‐annual hydrological variation affects horizontal motion to some extent (e.g., Kim et al., 2021). However, we assume that the data set mostly captures the interseismic deformation in the area and we take into account the existence of nonlinear deformation effects by increasing the uncertainties on the MIDAS velocities.…”
Section: Tectonic Context Of the Southwestern United States And Gnss ...mentioning
confidence: 99%